A dog with multiple fracture - Nuriza Zamirbekova; Fatma Çuhadar Erdal; Mustafa Arıcan (Eurasian Journal of Veterinary Sciences)
Aim: The material of this case was a mixed breed female dog approximately 10 months old, weighing 8 kg, brought to the surgery clinic. In the clinical examination was shown crepitation, dislocation, asymmetry and severe pain in both hind legs and paralysis in the left hind. Radiography of the pelvis and extremities revealed oblique fracture in the right corpus ilium, right and left pubis and ischium fractures, luxation in the left sacroiliac joint. Oblique fracture in the diaphysis of the right femur and tibia, Salter Harris type IV fracture in the left femur and elbow luxation in the left forelimb was also observed. According to laboratory results, severe metabolic acidosis, base deficit, leukocytosis and hyperlactatemia were determined. The fluid and medical treatment was started immediately. The dog was initially stabilized in the intensive care unit before surgery. Surgical approaches for corpus ilium fracture was performed laterally. A lateral reconstruction plate was placed. The femoral fractures of both hind limbs were approached cranio-laterally. Fixation of the right and left femur fractures was achieved with locking compression plate. Locking compression plate with 8-hole was placed for the tibia fracture fixation by cranio-medial approach. Two cancelous screw was placed into the lateral condyle of the humerus and the caput of the radius for elbow. Post-operative observation of the patient was carried out for 4 weeks and discharged postoperatively. In multiple fracture cases, the operative procedure is decided by making classifications according to the fracture evaluation criteria (mechanical, biological and clinical) after providing life functions.